O cultivar da legalidade: articulações digitais, políticas e morais para legalização da maconha medicinal em Natal - Silva, Ioanna Augusta Costa da (2021)
Seeing a Brazilian scenery of increasing visibility and popular claim for the legalization of marijuana for medical purposes, this paper fulfills the purpose of presenting a research on this social mobilization in the city of Natal. Aiming to follow these mobilizations, and based on a participating observation, the WhatsApp group Liga Canábica-RN was monitored, as well as events, lectures and other online and face-to-face activities, which are spaces for sociability, information and political agency related to themes that deals with the use and consumption of spp Cannabis. Thus, the research gets across themes like consumption, health, and cyberculture to comprehend what is this articulation network - which has many members and diverse political strength - and aims to make its benefits and contribution to the legality status of the plant visible.